AN ANALYSIS ON USING FACEBOOK AS A SUPPORTING MEDIA IN COLLEGE (STUDY ON COURSE INTRODUCTION TO ANTHROPOLOGY ON THE STUDY PROGRAM OF SOCIOLOGY ANTHROPOLOGY SEBELAS MARET UNIVERSITY) - Puspitaningsih, Lestari; Sawiji, Hery; Rahmanto, Andre Novie (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
The purpose of this study is, 1) to determine the use of facebook as a medium supporting distance learning course on Introduction to Anthropology on program Sociology Anthropology of Education Program in 2012, 2) To know the benefits of facebook as a medium supporting distance learning course on Introduction to Anthropology Education Program Sociology Anthropology in 2012, 3) To determine the barriers and the efforts to handle the media supporting distance learning course on Introduction to Anthropology on program Sociology Anthropology Educational Studies academic year 2012.This study used a qualitative approach and study research. The data source is the informant, place and events, archives, respondents, and document analysis. The sampling technique used was snowball sampling. Method of collecting the data is interviews and documentation analysis. The validity of data using triangulation data (source), while the analysis of the data using interactive analysis.Based on the analysis it can be concluded: (1) Implementation of the Learning Activities by Leveraging Social Media Facebook as a Learning Support. Facebook is not only used as a medium of support but also be used in full for one semester, as a lecturer abroad. Facebook is used as a medium for distance learning because almost all students use facebook. Facebook is used for communication between faculty and students and among students to discuss courses, announcing assignments and exams so that all members can see all the information on group. 2) Excellence in Learning by Using Facebook as a Media Support Distance Learning: a) Increasing levels of interaction between students with learning educators, b) Enables the interaction of learning from anywhere and at any time, c) Reaching learners in coverage, d) Increasing activity in the learning activities. 3) Obstacles in Learning Using Facebook as a Media Support Distance Learning: a) The difference in speed access and delays with predetermined targets, b) error application, c) Lack of character, d) inadequate facilitiesTo cope with such the. From the above it can be an obstacle in efforts to minimize these barriers is to: a) The material should be concise and clear, and not too much, b) provide respite deadlines and provide confirmation.Keywords: media, facebook, college